Increased prevalence of HCV and hepatic decompensation in adults with psoriasis: a population-based study in the United Kingdom - Noe, M. H. (J Eur Acad Dermatol Venereol, 2017)
BACKGROUND: The hepatitis C virus (HCV) is a major cause of global morbidity and mortality, with conflicting evidence regarding a possible association with psoriasis. OBJECTIVE: To determine the prevalence of HCV in psoriasis patients, compared to controls, and determine the incidence of hepatic decompensation in HCV+ psoriasis patients compared to HCV+ controls. METHODS: Cross-sectional and cohort studies were conducted in The Health Improvement Network (THIN). RESULTS: In fully adjusted models, a statistically significant increase in prevalence was seen in the adults with psoriasis (OR: 1.24, 95% CI 1.10 – 1.40). A “dose-response” of HCV prevalence with increasing psoriasis severity was not observed. HCV+ patients with psoriasis had a non-statistically significant increased incidence of hepatic decompensation compared to HCV+ individuals without psoriasis (aHR: 1.58, 95% CI: 0.90– 2.77). The risk was highest, and statistically significant, in those with moderate to severe psoriasis (aHR: 21.51, 95% CI: 7.58–61.03). CONCLUSIONS: These results demonstrate a higher prevalence of HCV in adults with psoriasis and a higher rate of hepatic decompensation in HCV+ individuals with moderate-severe psoriasis.